17% efficiency all-small-molecule organic solar cells enabled by nanoscale phase separation with a hierarchical branched structure. Issue 11 (27th September 2021) - Qin, Jinzhao; Chen, Zhihao; Bi, Pengqing; Yang, Yang; Zhang, Jianqi; Huang, Ziyun; Wei, Zhixiang; An, Cunbin; Yao, Huifeng; Hao, Xiaotao; Zhang, Tao; Cui, Yong; et al.
Abstract : By constructing a ternary cell with a B1:BO-2Cl:BO-4Cl donor:acceptors combination, an outstanding power conversion efficiency (PCE) of 17.0% (certified to be 16.9%) has been realized for all-small-molecule organic solar cells (ASM-OSCs). Abstract : For all small-molecule-based organic solar cells (SM-OSCs), it is very challenging to obtain a nanoscale bicontinuous network structure in the active layers, so their power conversion efficiencies (PCEs) still lag behind those of the polymer-based OSCs. In this work, highly efficient SM-OSCs based on a ternary bulk heterojunction (BHJ) layer of B1:BO-2Cl:BO-4Cl were constructed. Ternary cells with the three different BO-2Cl:BO-4Cl weight ratios exhibit higher PCEs than those of B1:BO-2Cl- and B1:BO-4Cl-based binary cells. The results obtained from the transient absorption, time-resolved photoluminescence spectroscopy and device physics analysis reveal that the ternary cell with the optimal composition (B1:BO-2Cl:BO-4Cl = 1 : 0.5 : 0.5 in weight ratio) exhibits faster charge transfer processes, suppressed geminate and non-geminate charge recombination, lower energetic disorder, and higher and more symmetric carrier mobilities than the two binary cells. The transmission electron microscopy measurement results reveal that the nanoscale bicontinuous interpenetrating network with a hierarchical branched structure can be fully evolved in the BHJ layer with the optimal ternary composition. As a result, the optimal ternary cell exhibits a PCE of 17.0% (certified to be 16.9%) and a fill factor of 0.78, which are the highest values obtained for SM-OSCs.